The problems of orphans of unknown parentage and their needs in the light of the life model - Al-Harthy, Bayan Abdullah; Al-Zahrani, Asma Ali (Journal of Humanities & Social Sciences, 2022)
This theoretical article aims to highlight the care of orphans of unknown descent through their care in Islam, in Saudi Arabia, and in international law, it is worth mentioning that this group is the neediest and most vulnerable to problems and therefore calls for the need to intervene and address these problems to reduce their appearance, social service as a humanitarian profession contributes to addressing problems in its various ways and therapeutic interventions to deal with them, through this article we will present professional intervention with orphans of unknown proportions in light of the model of Life by focusing on several basic axes:- Life model goals with orphans of unknown proportions.- Life model assumptions.- Stages of professional intervention in the life model with orphans of unknown descent.- Roles of a social worker with orphans of unknown descent.
Keywords: unknown parentage; orphans; welfare; life model